Enhancing E-Learning System through Learning Management System (LMS) Technologies: Reshape the Learner Experience - Abaricia, Cecilia P.; Delos Santos, Manuel Luis C. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This paper aims to determine how the LMS Web portal application reshapes the learner experience through the developed E-Learning Management System using Data Mining Algorithm. Method – The methodology that the researchers used is descriptive research involving the interpretation of the meaning or signiﬁcance of what is described. Gather data from questionnaires, surveys, observations concerned with the study, and the chi-square formula for the statistical treatment of data. Results – The ﬁndings of the study, the extent that LMS Web portal application reshapes the learner experience in terms of the following variables with the Average Weighted Mean (AWM): Flexible engagement of Learners in any device is highly satisﬁed; Personalize learning tracker is highly satisﬁed; Collaborating with the Learning Expert is highly satisﬁed; Provides user-friendly Teaching Tools is satisﬁed; Evident Learner Progress and Involvement and is satisﬁed. Conclusion – In the final analysis, this E-Learning System can ﬁt any educational needs as follows: chat, virtual classes, supportive resources for the students, individual/group monitoring, and assessment using LMS as maximum eﬃciency.  Moreover, this platform can be used to deliver hybrid learning. Recommendations – This LMS Web portal application is recommended for hybrid learning that helps to reshape the learner experience. Research Implications – Through these platforms, learners provide an ease and flexible learning experience as self–paced learners.  Students may work independently on their learning, updating on the students’ performances and school announcements for the activities and events.